The association between the social environment of childhood and adolescence and depression in young adulthood:a prospective cohort study - Kehusmaa, J. (Johanna); Ruotsalainen, H. (Heidi); Männikkö, N. (Niko); Alakokkare, A.-E. (Anni-Emilia); Niemelä, M. (Mika); Jääskeläinen, E. (Erika); Miettunen, J. (Jouko) (Elsevier, 2022)
Abstract Background: Good social relationships with parents and peers protect children and adolescents from developing mental disorders in adulthood while several negative experiences increase the risk of depression in later life. Methods: We used population-based cohort data from the Northern Finland Birth Cohort (NFBC) 1986. Participants (n = 6147), their teachers and parents reported factors associated with the social environment of children and adolescents. Diagnoses of depression of cohort members were derived from Finnish nationwide registers. We conducted regression analyses to assess which factors of the social environment of childhood and adolescence were associated with depression in young adulthood. Results: Bullying victimization in adolescence was the strongest predictor of depression in young adulthood among girls (OR 2.23: 95% CI 1.47–3.39) and boys (OR 2.44: 95% CI 1.49–4.00). Loneliness and bullying behavior in childhood were associated with depression in boys only. Loneliness in adolescence (OR 1.63: 95% CI 1.30–2.04) was associated with depression among both genders. Spending with the family seemed to protect against the negative impact of bullying and loneliness. Limitations: We used single-item study questions to measure social relationships. These questions do not necessarily describe the phenomena as accurately as the measures validated for them. Conclusions: Problems in social relationships with peers in childhood and adolescence are associated with depression in young adulthood. Time spent with the family is emphasized in situations in which adolescents have problems in peer-relationships.